Synthesis and Characterization of New Eco-Friendly Fire-Retardants Based on Soda-Silicate Glass - Ngoc Nguyen Nguyen; Vinh The La; Thanh Xuan Le; Suong Thu Huynh (Department of Chemical Engineering, Universitas Gadjah Mada, 2020)
Fire-retardants (FRs) are additives used to improve the fire-resistance of combustible materials. New generations of FRs must be effective and eco-friendly. Traditional inorganic FRs are non-hazardous but have limited fire-retardancy. Here, we aim to develop an innovative way to enhance the fire-retardancy of inorganic FRs. We synthesized a new type of FRs, called mATH, whose compositions are similar to soda-silicate glass (xNa2O.yK2O.zSiO2.tAl2O3). When applied to unsaturated polyester resin, mATH showed a much better performance than traditional aluminum trihydroxide (ATH). The better performance of mATH originated from its new working mechanism. Dehydrated mATH, as a soda-silicate glass, melts under the heat of the fire, which causes heat sink and produces a molten glass. The molten glass forms a charred insulating layer that prevents oxygen from contacting the interior combustible materials. This phenomenon significantly contributes to the fire-retarding behavior of mATH. Our findings open a new method for developing effective eco-friendly FRs.